Revision of the helvetica-group of the genus Ceropales Latreille (Hym.: Ceropalidae). - Móczár, László (Contributions to Entomology = Beiträge zur Entomologie, 1989)
12 species are revised and 9 species described as new: Ceropales africana (female, male), C. angolaensis (female), C. dayi (female, male), C. ferugo (female, male), C. gambiae (female, male) und C. maliensis (female, male) (from tropical Africa); C. haupti (male) and C. indica (female, male) (from Asia) and C. australensis (female, male) (from Australia). New females of C. lawrencei Arnold and C. spinolai nom. nov., as well as new males of C. waltoni Arnold and C. helvetica bogdoensis Moczar are described for the first time. C. sponolai nom. nov. for the homonym C. interrupta Spinola. Lectotypes are designated and holotypes are confirmed. On the basis of the original material new synonyms are established: C. diversipes Haupt (female) and C. picturatus Haupt (male) jun. syn. = C. kriechbaumeri Magretti; C. fulvus Haupt (female, male) jun. syn. = variolosa Arnold and C. sabulicola Priesner (female, male) jun. syn. = juncoi Giner. A key and new distributional data are given.Nomenclatural Actsafricana Móczár, 1989 (Ceropales), spec. n.angolensis Móczár, 1989 (Ceropales), spec. n.australensis Móczár, 1989 (Ceropales), spec. n.dayi Móczár, 1989 (Ceropales), spec. n.diversipes Haupt, 1962 (Ceropales), syn. n. of Ceropales kriechbaumeri Magretti, 1884ferrugo Móczár, 1989 (Ceropales), spec. n.fulvus Haupt, 1962 (Ceropales), syn. n. of Ceropales variolosa Arnold, 1937gambiae Móczár, 1989 (Ceropales), spec. n.haupti Móczár, 1989 (Ceropales), spec. n.indica Móczár, 1989 (Ceropales), spec. n.judicatrix Nurse, 1902 (Ceropales), Lectotypekarooensis Arnold, 1937 (Ceropales), Lectotypekriechbaumeri Magretti, 1884 (Ceropales), Lectotypeligea Bingham, 1903 (Ceropales), Lectotypemaliensis Móczár, 1989 (Ceropales), spec. n.multipicta Arnold, 1937 (Ceropales), stat. n. described as Ceropales karooensis sspec. multipictapicturatus Haupt, 1962 (Ceropales), syn. n. of Ceropales kriechbaumeri Magretti, 1884sabulicola Priesner, 1955 (Ceropales), Lectotype; syn. n. of Ceropales juncoi Giner, 1945spinolai Móczár, 1989 (Ceropales), nom. n. pro Ceropales interrupta Spinola, 1838, nec Say, 1837waltoni Arnold, 1937 (Ceropales), stat. n. described as Ceropales karooensis sspec. waltoni